Eficiência de Inseticidas no Controle de Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) e seus Efeitos sobre a Qualidade e Produtividade da Cana-de-Açúcar - Dinardo-Miranda, Leila; Pivetta, João; Fracasso, Juliano (BioAssay, 2009)
The objective of this work was to evaluate the efficiency of some insecticides for controlling root froghopper, Mahanarva fimbriolata (Stål), and their effects on sugarcane quality and yield. Two experiments were carried out under field conditions to test the insecticides imidacloprid at 480, 720 or 960 g of active ingredient (AI).ha-1, aldicarb at 1,200 or 1,500 g AI.ha-1 and thiamethoxam at 150 or 200 g AI.ha-1, in comparison with the control (without insecticide). In one of the experiment, the treatments were applied when root froghopper infestation was 3.4 insects per meter. In this experiment, imidacloprid and thiamethoxam reduced pest infestations for at least 121 days. In another experiment, the insecticides were applied when froghopper infestation was 9.6 insects per meter. Best control was obtained with aldicarb at 1,500 g AI.ha-1 while thiamethoxam and imidacloprid reduced pest infestations only when they were applied at higher doses. The reduction of pest infestation with insecticides applications did not affect the sugar content in the stalks or fiber, but increased the sugarcane yield, reaching values up to 15.3 t.ha-1.